Analysis of Work Facilities, Work Discipline, and Work Communication on the Performance of ASN Employees at the Ministry of Religion Office of North Sumatra Province - Nabila Azhari; Abdi Setiawan; Teguh Wahyono (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the effects of work facilities, work discipline, and work communication on the performance of civil servant employees at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province. The study used a quantitative approach with an associative method. The research population consisted of 247 civil servant employees, with a sample of 71 respondents selected using the Slovin formula and a purposive sampling technique. Primary data were obtained through the distribution of questionnaires, and the results were processed using SPSS software version 24. Data analysis was conducted using multiple linear regression to examine the relationships between the independent variables and the dependent variable. The results showed that work facilities, work discipline, and work communication, both partially and simultaneously, had positive and significant effects on employee performance. Work discipline became the most dominant variable influencing employee performance, as indicated by the highest regression coefficient. The coefficient of determination (adjusted R²) of 0.950 indicated that 95.0% of the variation in employee performance could be explained by the three independent variables, while the remaining 5.0% was explained by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was categorized as very strong, with a correlation coefficient (R) value of 0.976.